PSYCHOMETRIC PROPERTIES OF THE INVENTORY OF COLLEGE STUDENTS’ RECENT LIFE EXPERIENCES (ICSRLE): LITHUANIAN VERSION - Ieva Peciuliene; Aidas Perminas; Loreta Gustainiene; Dovile Valiune (European Scientific Journal, ESJ, 2015)
Objective. Although health care professionals have been interested in the phenomenon of stress for decades, many researchers agree that this issue has not been given enough attention, especially when it comes to stress measurement methods in different cultural settings and different population groups. The aim of the study was to investigate psychometric properties of the Lithuanian version of ICSRLE and to compare these results with the original scale. Methods. 437 students had participated in the study by filling the questionnaires voluntarily. Age of participants ranged from 18 to 32 years. Results. Psychometric properties of the Lithuanian version of ICSRLE demonstrated statistically acceptable level of internal and external reliability of the scale and the subscales. The Lithuanian version of the scale demonstrated statistically acceptable levels of content and construct validity as well. Exploratory and confirmatory factor analyses revealed a different 6- factor structure of the scale using 36 items. The scale structure included the following dimensions: relationships problems, lack of time, social alienation, future decisions, academic dissatisfaction, financial problems. 13 items of the original scale did not correspond to the 6-factor structure. Conclusions. The structure of 6 factors was a better fit for the Lithuanian students than the original structure of 7 factors.